PENERAPAN UNSUR KEALPAAN DALAM PROSES PENYIDIKAN TINDAK PIDANA KECELAKAAN LALU LINTAS - Yuliantoro Yuliantoro (Jurnal Hukum, 2019)
This study aims to determine the application of the element of negligence in the process of investigating traffic accidents and to find out the obstacles in the application of the negligence element in the traffic accident investigation process. The method used is the normative juridical approach. Normative research or also known as library law research is legal research carried out by examining library material or secondary data only, then to be applied to research problems, namely the application of negligence elements in the process of investigating traffic accidents, so that its presentation stems from the principles and theories and doctrines as well as applicable legislation. Based on the research it can be concluded that 1) the application of the Traffic Accident Crime is when the relationship between the inner perpetrator and the consequences arising from the act or there is an outward relationship which is a causal relationship between the offender's actions and the prohibited consequences, so that the suspect can be applied elements negligence resulting in the death of another person and 2) Obstacles in the application of the Traffic Accident Crime is the opinion of the suspect and the public in general that accidents that occur on the highway are pure accidents and cannot be criminally accounted for so that the community, especially victims, will forgive the suspect in this crime of negligence.